Response of long‐term water availability to more extreme climate in the Pearl River Basin, China. (9th November 2016) - Li, Jianfeng; Zhang, Lu; Shi, Xiaogang; Chen, Yongqin David
ABSTRACT: Under global warming, increasing temporal variability of climatic factors at various timescales (e.g. from inter‐daily to inter‐annual) has been reported in many places of the world over the past decades. The changes of temporal variability can be characterized by more extreme climate, such as more frequent and intensive heavy precipitation, less light rain days, and longer dry spells. These changes can subsequently bring about more frequent and intensive hydrologic extremes, including floods and droughts. This study shows that increase in inter‐daily variability of precipitation and temperature not only triggers more intensive hydrologic extremes, but also causes considerable impacts on long‐term water availability. Sixteen climate scenarios are designed to separate overall changes of precipitation and temperature into two aspects: (1) change in monthly mean and (2) change in inter‐daily variability. Runoff of the Pearl River Basin (PRB) is simulated by the variable infiltration capacity (VIC) model under these scenarios. The results indicate that increase in inter‐daily variability of the climate alone can lead to considerable increase in long‐term water availability with reduced actual evapotranspiration (AET). The simulations also show that the inter‐daily interaction between precipitation and temperature (i.e. lower temperature on a rain day) is important for long‐term hydrologic simulations. The changing directions of simulated AET under scenarios with this interaction are opposite to those under scenarios without the interaction.